The Influence of Lecturers' Persuasive Communication on Self-Confidence and Learning Motivation of Buddhist College Students - Sidartha Adi Gautama; Wistina Seneru; Widiyanto Widiyanto; Ayu Andriyaningsih; Ine Yudhawati (Syntax Corporation, 2023)
This quantitative research aims to determine the contribution of lecturers' persuasive communication to students' self-confidence and learning motivation. The study population was students of Jinarakkhita Buddhist College of Lampung. The sampling technique was carried out by random sampling with the number of selected samples as many as 78 people. The research data were collected using the lecturer's persuasive communication scale, self-confidence scale, and learning motivation scale. The data analysis technique used was multivariate analysis of variance (MANOVA). Analysis of research data showed that there was a positive contribution between persuasive communication and self-confidence. It is also known that there is a positive contribution between persuasive communication and learning motivation. Specifically, it is known that in this study, lecturers' persuasive communication is high, students' self-confidence is moderate, and students' learning motivation is also moderate.